2016
DOI: 10.1186/s12885-016-2306-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of ablative margins by the intraoperative use of CEUS-CT/MR image fusion in hepatocellular carcinoma

Abstract: BackgroundTo assess whether intraoperative use of contrast-enhanced ultrasound (CEUS)-CT/MR image fusion can accurately evaluate ablative margin (AM) and guide supplementary ablation to improve AM after hepatocellular carcinoma (HCC) ablation.MethodsNinety-eight patients with 126 HCCs designated to undergo thermal ablation treatment were enrolled in this prospective study. CEUS-CT/MR image fusion was performed intraoperatively to evaluate whether 5-mm AM was covered by the ablative area. If possible, supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…The method of CEUS- CT/MR image fusion used in this study had been reported in our former article [18]. The CT/MR image series in DICOM format were transferred into the navigation system and 3D image volume was generated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of CEUS- CT/MR image fusion used in this study had been reported in our former article [18]. The CT/MR image series in DICOM format were transferred into the navigation system and 3D image volume was generated.…”
Section: Methodsmentioning
confidence: 99%
“…The term “ablative margin” refers to the 0.5 to 1.0-cm-wide region of normal tissue around the tumor that should ideally be removed during tumor ablation [16, 17]. Therefore, AM is one of the most important factors for the prediction of LTP in HCC patients after RFA [1820]. However, regular medical imaging methods, including CT, MR, and contrast-enhanced ultrasound (CEUS), are not able to accurately evaluate AM because the tumor and surrounding normal liver tissue mix and merge in the ablative area, and the boundary between normal tissue and the ablative area is difficult to identify.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the application of fusion imaging between CT/ MRI and US (CT/MRI-US fusion imaging) for the detection, guidance and evaluation during liver cancer thermal ablation [13][14][15][16][17][18][19][20]. Our previous studies [16,21,22] have also demonstrated that CT/MRI-CEUS fusion imaging is a feasible and accurate method for immediately assessing the treatment response of thermal ablation. The target tumor and 5-mm ablative margin can be depicted in preprocedural CT/MRI images; by overlapping these images with real-time CEUS, operators can intuitively determine whether the target tumor and its ablative margin can be encompassed by the avascular zone.…”
Section: Introductionmentioning
confidence: 99%
“…We have successfully reported the application of contrastenhanced US (CEUS)-CT/MRI fusion imaging for determining AM after the radiofrequency ablation (RFA) of hepatocellular carcinoma (HCC). CEUS-CT/MRI fusion imaging is helpful in the guidance and assessment of the RFA procedure [10,11]. However, our previous experience has shown that US-CT/MRI fusion imaging is not sufficiently convenient during the ablation procedure.…”
Section: Introductionmentioning
confidence: 99%